Analisis Ketepatan Penetapan Tarif Layanan Rawat Jalan Poli Penyakit Dalam Melalui Perhitungan Unit Cost dengan Pendekatan Activity Based Costing (Studi Kasus Rumah Sakit Universitas Brawijaya) - Maghfiroh, Nur Rahmadhona Shobiqatul; Erwin Saraswati (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study is motivated by the potential mismatch between bundled service tariffs and the actual costs incurred by hospitals, particularly in the Internal Medicine Outpatient Clinic, which has a high patient volume and contributes significantly to hospital revenue. The problem examined in this study is the calculation of unit costs for services in the Internal Medicine Outpatient Clinic at Universitas Brawijaya Hospital using the Activity-Based Costing (ABC) method. This research employs a qualitative research method with a case study approach. The sampling technique used is purposive sampling of five types of services with the highest frequency. Data were collected through interviews, observations, and documentation studies of the hospital’s financial and operational data. The analysis was conducted by identifying activities, determining cost drivers, accumulating costs for each activity center, and calculating the unit cost of each service. The results indicate that the unit costs calculated using the ABC method for all services studied are lower than the prevailing tariffs, with an average difference of 41.05%. These findings suggest the presence of overpricing in service tariffs, which may reduce competitiveness and public interest. This study concludes that the Activity-Based Costing method is able to provide more accurate cost information as a basis for determining hospital service tariffs.